Pelatihan Guru-Guru PAUD “MELEK” Teknologi Kabupaten Simalungun - Windarto, Agus Perdana; Parlina, Iin; Wanto, Anjar (Jurnal TUNAS, 2019)
This community service aims to improve the knowledge and skills of PAUD teachers specifically software-based and android interactive learning in Simalungun District. This dedication was held during July 2019. This activity was carried out in two days, starting at 08.00- 11.30 WIB (first session), 14.00- 16.30 WIB (second session), on Saturdays, 20 and 27 July 2019, the location of the service was held in kindergarten Sandy Putra Pematangsiantar. The target of this activity is PAUD teachers in Simalungun District. The reason for the selection of service locations was deliberations from representatives of PAUD partner management in Simalungun District. For teachers, PAUD provides transportation to be taken to the location of the service given that this activity has a responsibility for PAUD teachers in educating the children of the nation in the industrial revolution era 4.0. The method used in the implementation is with presentations / lectures, discussions, questions and answers, and simulations / exercises. The results of this community service activity showed that of the 40 participants, PAUD teachers were able to answer all questions with a number of questions 45% (18 participants) after conducting training which previously were only able to answer 9 questions correctly as many as 13% (5 participants) before being asked for training. Therefore, in the future it is expected that further training can be carried out by PAUD teachers so that they can utilize knowledge more optimally and implement it more easily by their students.